The role of ferroptosis and oxidative stress in cognitive deficits among chronic schizophrenia patients: a multicenter investigation - Zhenlei Peng; Qiyu Jia; Junxiong Mao; Shijie Jiang; Qi Ma; Xiao Luo; Zhiguo An; Anqi Huang; Chuang Ma; Qizhong Yi (Schizophrenia)
Abstract Oxidative stress (OS) is crucial in schizophrenia (SCZ) pathology. Ferroptosis, a recently discovered cell death pathway linked to OS, might contribute to the development of SCZ. This study investigated the association between ferroptosis markers and cognitive impairments in chronic SCZ patients. A retrospective analysis was conducted on 204 chronic SCZ patients with cognitive deficits and 216 healthy controls (HC) matched for relevant characteristics. Plasma levels of ferroptosis and OS markers, including iron, ferritin (FE), transferrin (TF), glutathione peroxidase 4 (GPX4), long-chain acyl-CoA synthetase 4 (ACSL4), glutathione (GSH), sirtuin 1 (SIRT1), nuclear factor erythroid 2-related factor 2 (Nrf2), malondialdehyde (MDA), and superoxide dismutase (SOD) were measured. Standardized assessments like the positive and negative syndrome scale (PANSS), and Montreal Cognitive Assessment (MoCA) were used to evaluate psychiatric symptoms, and cognitive function. SCZ patients showed significant differences in markers compared to the HC group (P < 0.01). Multiple linear regression analysis revealed that decreased GSH and iron levels, along with elevated SOD levels, were significantly associated with the overall severity of psychiatric symptoms. Additionally, reduced GPX4 levels and increased ACSL4 and FE levels were significantly linked to negative symptoms and cognitive impairments. Notably, GPX4 emerged as a key predictor for cognitive function in abstraction and language domains. Our study revealed alterations in the altered plasma levels of GPX4, GSH, iron, ACSL4, FE, and SOD in chronic SCZ patients, which might indicate a close association between biomarkers of ferroptosis and OS and the psychiatric symptoms and cognitive deficits observed in these individuals.